The Importance of the Collection of Oskar Kolberg for Contemporary Choreological Studies - Nowak Tomasz (Musicology Today, 2014)
The mainstream fields of Polish dance research were defined in 1818–1847 by Józef Elsner, Kazimierz Brodziński, Łukasz Gołębiowski and Karol Czerniawski, who broadly characterized some elements of the dances considered as national (the polonaise, mazur, krakowiak and kozak). Oskar Kolberg knew very well the works of all these authors and referred to them many times. However, he was unique in his extensive documentation of dance melodies, information about their geographic origin, and local terminology. He also characterized the dances with regard to their sequence in the traditional context and described the dance technique in an instructive manner.